Hayabusa2 extended mission: New voyage to rendezvous with a small asteroid rotating with a short period. Issue 3 (1st August 2021) - Hirabayashi, M.; Mimasu, Y.; Sakatani, N.; Watanabe, S.; Tsuda, Y.; Saiki, T.; Kikuchi, S.; Kouyama, T.; Yoshikawa, M.; Tanaka, S.; Nakazawa, S.; Takei, Y.; et al.
Highlights: Hayabusa2 plans its extended mission to rendezvous with 1998 KY26 in 2031. We show science assessments to select the final two candidates, 1998 KY26 and 2001 AV43. The mission will explore the origin and evolution of small bodies and planetary defense. Abstract: Hayabusa2 is the Japanese Asteroid Return Mission and targeted the carbonaceous asteroid Ryugu, conducted by the Japan Aerospace Exploration Agency (JAXA). The goal of this mission was to conduct proximity operations including remote sensing observations, material sampling, and a Small Carry-On Impact experiment, as well as sample analyses. As of September 2020, the spacecraft is on the way back to Earth with samples from Ryugu with no critical issues after the successful departure in November 2019. Here, we propose an extended mission in which the spacecraft will rendezvous with a small asteroid with ~30 m - ~40 m in diameter that is rotating at a spin period of ~10 min after an additional ~10-year cruise phase. We introduce that two scenarios are suitable for the extended mission. In the first scenario, the spacecraft will perform swing-by maneuvers at Venus once and Earth twice to arrive at asteroid 2001 AV43. In the second scenario, it will perform swing-by maneuvers at Earth twice to reach asteroid 1998 KY26. In both scenarios, the mission will continue until the early 2030s. JAXA recently released the decision that the spacecraft will rendezvous with 1998 KY26. This paper focuses on our scientific assessments of the two scenarios but leaves the decision process to go to 1998 KY26 for future reports. Rendezvous operations will be planned to detail the physical properties and surrounding environments of the target, one of the smallest elements of small planetary bodies. By achieving the planned operations, the mission will provide critical hints on the violent histories of collisions and accumulations of small bodies in the solar system. Furthermore, the established scientific knowledge and techniques will advance key technologies for planetary defense.